2014
DOI: 10.1165/rcmb.2012-0519oc
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide Phosphoribosyltransferase Inhibitor Is a Novel Therapeutic Candidate in Murine Models of Inflammatory Lung Injury

Abstract: We previously identified the intracellular nicotinamide phosphoribosyltransferase (iNAMPT, aka pre-B-cell colony enhancing factor) as a candidate gene promoting acute respiratory distress syndrome (ARDS) and ventilator-induced lung injury (VILI) with circulating nicotinamide phosphoribosyltransferase potently inducing NF-kB signaling in lung endothelium. iNAMPT also synthesizes intracellular nicotinamide adenine dinucleotide (iNAD) in response to extracellular oxidative stress, contributing to the inhibition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 25 publications
2
24
0
Order By: Relevance
“…The genetic association of NAMPT promoter SNPs with ARDS was replicated in a separate ARDS cohort and was found to be associated with the number of ventilator-free days and overall ARDS mortality (12). Finally, novel ARDS therapeutic strategies designed to reduce NAMPT enzymatic activity or bioavailability in preclinical models of ARDS and VILI resulted in significant VILI protection (11,13). These studies, highlighting the intimate involvement of NAMPT activity/expression in ARDS/VILI susceptibility and severity, led us to explore the molecular regulation of NAMPT promoter activity.…”
Section: Clinical Relevancementioning
confidence: 94%
“…The genetic association of NAMPT promoter SNPs with ARDS was replicated in a separate ARDS cohort and was found to be associated with the number of ventilator-free days and overall ARDS mortality (12). Finally, novel ARDS therapeutic strategies designed to reduce NAMPT enzymatic activity or bioavailability in preclinical models of ARDS and VILI resulted in significant VILI protection (11,13). These studies, highlighting the intimate involvement of NAMPT activity/expression in ARDS/VILI susceptibility and severity, led us to explore the molecular regulation of NAMPT promoter activity.…”
Section: Clinical Relevancementioning
confidence: 94%
“…In this study, we evaluated the effects of imatinib in the well-established murine models of LPS (IT)-and H TV MV (VILI)-induced ALI. As we have previously described, the LPS model is characterized by increased vascular leakage and activation/recruitment of neutrophils to the inflamed lungs (41), whereas the VILI model (VT: 30 ml/kg) is characterized by more modest increases in pulmonary vascular leak and neutrophil lung recruitment (35). To investigate the effects of imatinib on LPS-or VILI-induced alveolar-capillary permeability, we first measured the concentration of protein in BAL.…”
Section: Effects Of Imatinib On Lung Vascular Leak In Lps and Vili Mumentioning
confidence: 99%
“…In addition, in rats visfatin participates in inflammatory processes in the spleen by modulating both anti-inflammatory and proinflammatory cytokines, such as IL-4, IL-6, TNF, and IL-10, and contributes to apoptosis in the spleen via the mitochondrial pathway [16]. In a study involving rats, the myocardial expression of visfatin increased after the injection of LPS, and the co-administration of a visfatin inhibitor reduced myocardial inflammation and damage and improved cardiac function [14]. Similarly, a visfatin inhibitor attenuated the LPSinduced pulmonary cytokine levels and improved the lung injury scores of mice [15].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the central injection of visfatin induces anorectic and febrile responses by enhancing the expression levels of hypothalamic pro-inflammatory cytokines [6], indicating that visfatin might be related to the development of such symptoms in under acute inflammatory conditions. It has been reported that visfatin promotes lung damage and myocardial impairment under acute inflammatory conditions and that the inhibition of visfatin attenuates these disorders [14,15]. In addition, it has been shown that visfatin participates in inflammatory responses in the spleen [16].…”
Section: Introductionmentioning
confidence: 99%